Targeting astrocytes polarization after spinal cord injury: a promising direction - Li, Helin; Liu, Ying; Sun, Yucao; Guo, Hangyu; Lv, Shiyan; Guo, Wenhui; Ren, Jiyu; Wang, Yufu; Zu, Jianing; Yan, Jinglong; Wang, Nanxiang (Frontiers in Cellular Neuroscience, 2024)
Spinal cord injury (SCI) is a serious neurological injury that causes severe trauma to motor and sensory functions. Although long considered incurable, recent research has brought new hope for functional recovery from SCI. After SCI, astrocytes are activated into many polarization states. Here we discuss the two most important classical phenotypes: the 'A1' neurotoxic phenotype and the 'A2' neuroprotective phenotype, with A1 astrocytes being neurotoxic and impeding neurorecovery, and A2 astrocytes being neuroprotective. This paper discusses the changes in astrocyte responsiveness after SCI and the pros and cons of their polarization in SCI. It also elucidates the feasibility of astrocyte polarization as a therapeutic target for neuroprotection. In the future, multiple intervention strategies targeting astrocyte polarization are expected to gain wider clinical application, ultimately improving motor-sensory function and quality of life in SCI patients.Astrocyte Modulation in Spinal Cord Injury. Cells, 13.